(3cJGH aj GdWHs
(3ChdgG (B:s
(3eHJhQ GdChd eG ajg(B: (3Yed fHV GdUMjM hGdCbSGe GdJSYI GdePchQI, hEPG QcHJ cGfJ SHYI hYTQjf, hGdJQcjH EeG KfGFi Ch KdGKj SJMGdI GdQHGYi s
(3BNQgG (B:s
(3dchfg JMQjckG ecGfjkG, heLGQ VjbI JMJGL Edi ReGf cKjQ , hgh ReGf jJQbb ajg bhGe GdeGOI ahgGJ GdeLGQj hjJHNQ efg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B201 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs